ANALISIS SWOT DAN AHP SEBAGAI ACUAN STRATEGI OPTIMASI STUDENT BODY - Gendro Wiyono; Henny Welsa; Prayekti Prayekti (Jurnal Riset Bisnis dan Manajemen, 2019)
The purpose of this research is to find out how to build competitive strategy of higher education institution, and also to know the preference of students to make their choice in a college. The research method applied mix method that is the combination of quantitative and qualitative methods. The sample uses informant validated by 72 respondents. The analysis technique used in this research is SWOT method, with Cochran Q Test technique to test the SWOT identification perception similarity. To know student preference, this research uses Analytic Hierarchy Process (AHP) method. The results of this reseach showed that the position of the institution in the SWOT quadrant is already being known, also known the segmentation of students with different preferences. Implications of the findings of this research showed that: First, the development of strategies should take account of the quadrant positions; second, using the findings of student preferences for each segmentation as a basis for developing appropriate marketing strategies for each segmentation.